The reverse buffering effect of workplace attachment style on the relationship between workplace bullying and work engagement - Hamel, Jean-Félix; Iodice, Pierpaolo; Radic, Klara; Scrima, Fabrizio (Frontiers in Psychology, 2023)
Using the Job Demands-Resources model, this study investigates workplace attachment styles as predictors of work engagement and moderators of the well-established disengaging effect of workplace bullying. As a personal resource, we hypothesized that secure workplace attachment would foster work engagement, whereas both types of insecure workplace attachment (i.e., avoidant and preoccupied) would do the opposite. Previous work also led us to expect the relationship between workplace bullying and engagement to be stronger when targets expect it to act as job resource (i.e., secure workplace attachment) and weaker when their working model is consistent with workplace aggression – i.e., reverse buffering effects. Using the PROCESS macro, we tested these hypotheses in a convenience sample of French office employees (N = 472) who completed an online survey. Secure workplace attachment was associated with higher work engagement while insecure workplace attachment and bullying perceptions related negatively with work engagement. Supporting our hypotheses, feeling exposed to workplace bullying was most associated with disengagement in employees with a secure workplace attachment style and less so in others. Far from recommending insecure bonds as protection, our results rather highlight the need to prevent all forms of workplace aggression, thereby allowing employees to rely on their work environment as a job resource.